2009
DOI: 10.1158/1940-6207.capr-09-0028
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-like Growth Factor-I and Mammary Tumor Development inAd libitum–Fed, Chronic Calorie–Restricted, and Intermittent Calorie–Restricted MMTV-TGF-α Mice

Abstract: The effect of chronic (CCR) and intermittent (ICR) caloric restriction on serum insulin-like growth factor (IGF)-I levels and mammary tumor (MT) development was investigated. Tenweek-old MMTV-TGF-α female mice were assigned to ad libitum-fed (AL; AIN-93M diet), ICR [3-week 50% caloric restriction using AIN-93M-mod diet, 2× protein, fat, vitamins, and minerals followed by 3 weeks of daily 100% AL consumption of AIN-93M (∼75% of AL for each 6-week cycle)], and CCR (calorie and nutrient intake matched for each 6-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 64 publications
2
54
2
Order By: Relevance
“…The decreased serum leptin levels observed in our study were also observed in the calorie restricted, BK5.COX-2 18 and the MMTV-TGF-a mouse model of breast cancer. 30,31 Taken together, our findings show that both ICR and CCR were effective in delaying the progression of PanIN lesions to PDA and in reducing the incidence of PanIN-2 or greater lesions in LSL-Kras G12D ; Pdx-1/Cre mice. Lanza-Jacoby et al Calorie restriction prevents the development of pancreatic cancer 795 Importantly, ICR had a stronger protective effect on the development of lesions in the LSL-Kras G12D ; Pdx-1/Cre mice than did CCR by completely preventing PanIN-3 lesions.…”
Section: Discussionsupporting
confidence: 56%
“…The decreased serum leptin levels observed in our study were also observed in the calorie restricted, BK5.COX-2 18 and the MMTV-TGF-a mouse model of breast cancer. 30,31 Taken together, our findings show that both ICR and CCR were effective in delaying the progression of PanIN lesions to PDA and in reducing the incidence of PanIN-2 or greater lesions in LSL-Kras G12D ; Pdx-1/Cre mice. Lanza-Jacoby et al Calorie restriction prevents the development of pancreatic cancer 795 Importantly, ICR had a stronger protective effect on the development of lesions in the LSL-Kras G12D ; Pdx-1/Cre mice than did CCR by completely preventing PanIN-3 lesions.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, controlled refeeding had a similar effect to ad libitum refeeding on Mt development, as the Mt incidence of 10% was in the range of 3 and 15% previously reported for Icr mice that were allowed free access to food during refeeding in two earlier longitudinal studies (5,6). Additionally, a recently completed longitudinal study using the controlled refeeding protocol resulted in an Mt incidence rate of 9% for ICR mice compared to 71 and 35% for AL-fed and CCR mice (40). Integration of these findings suggest that the periods of severe restriction associated with the intermittent restriction protocol are important for the protective effect of Icr and that the refeeding aspect of the protocol does not influence the effect to any great degree.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, diet-induced obese (high calorie diet, fed ad libitum) mice exhibited increased leptin levels [128]. In this connection, our laboratory has been studying the impact No tumor tissue showed overexpression of estrogen receptor β, sex hormone-binding globulin (SHBG), epidermal growth factor receptor (EGFR), and p53 of caloric restriction in mammary tumorigenesis, particularly the protective role of intermittent caloric restriction [129][130][131][132]. In a recently completed study, we found that intermittent caloric-restricted mice had higher serum adiponectin and lower serum leptin levels after 64 weeks of caloric restriction.…”
Section: Preclinical Studies Of Both Leptin and Adiponectin In Relatimentioning
confidence: 99%